Respuesta :

Answer:

(5, 6)

Step-by-step explanation:

First, get both equations into slope-intercept form so they are easier to graph:

[tex]y=mx+b[/tex]

The first equation is already in this form, so only do the second equation:

[tex]x-y=-1[/tex]

To do this, just solve for y and that should almost always get it in the correct form.

[tex]\rightarrow x-y=-1\\\rightarrow -y=-x-1\\\rightarrow y=x+1[/tex]

That equation is also now in slope-intercept form.

Now, using the slope and y-intercept in both equations, you can graph them. Using the graph, you can see the solution of this system of equations at (5, 6).

Ver imagen cinderofsoulsss